Adsorption of Methylene Blue Dye on Urfa Stone Obtained Around at Agriculture Land in Harran Plain - Mehmet Fatih DİLEKOĞLU (Türkiye Tarımsal Araştırmalar Dergisi, 2018)
Urfa stone has been investigated as an alternative to current expensive methods of removing dyestuffs from wastewater, considering it can be used as a low cost, locally abundant, high-yielding and environmentally sensitive adsorbent. In this study, methylene blue (MB) dye removal potential of Urfa stone from the synthetically prepared wastewater, was investigated. Laboratory experiments were carried out as batches. Urfa Stone’s MB sorption performance was calculated with dosage (0.1, 0.25, 0.5 and 1 g) and initial concentrations (5, 10, 20, 30 and 40 mg L-1). Experiments were also performed for different pH values (3, 5, 7, 8, 8.98 and 11). Two kinetic models (pseudo second - order and pore diffusion) were used to calculate the adsorption ratios. The mechanism of adsorption by Lagergren equilibrium was also studied. Experimental data were analyzed using Langmuir, Freundlich and Tempkin isotherm models. As a result, it was understood that the adsorption of Methylene blue dye on the Urfa Stone was in full agreement with the Langmuir isotherm and ii partial agreement with the Tempkine isotherm. It was understood that the pseudo second - order kinetics and pore diffusion mechanisms can be applied to the kinetics of adsorption and the intraparticular diffusion rate was the effective mechanism. It was observed that the adsorption tends to occur spontaneously and the Urfa stone has a natural affinity to methylene blue dye. It has been understood that Urfa stone can be used as a natural, economical and environmentally friendly adsorbent.